2007
DOI: 10.1097/01.meg.0000250582.30737.bd
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of immunohistochemistry in gastric neuroendocrine (carcinoid) tumors

Abstract: (i) p53 immunoexpression associated with high proliferative rate was useful to distinguish between type I and type III gastric carcinoid tumors and (ii) these markers were able to predict a shorter survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Nishikura et al [4] showed that p53 overexpression was observed in 58.8% of gastric ECs, but not in gastric carcinoid tumors. Expression of p53 was associated with a high degree of cell proliferation (Ki-67-positive nuclear cells) and this marker also was able to predict a shorter survival time [5]. Thus, tumor progression is likely to accelerate cell proliferation, as reflected by the Ki-67 labeling index.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nishikura et al [4] showed that p53 overexpression was observed in 58.8% of gastric ECs, but not in gastric carcinoid tumors. Expression of p53 was associated with a high degree of cell proliferation (Ki-67-positive nuclear cells) and this marker also was able to predict a shorter survival time [5]. Thus, tumor progression is likely to accelerate cell proliferation, as reflected by the Ki-67 labeling index.…”
Section: Discussionmentioning
confidence: 95%
“…This hypothesis was supported by correlations between the pattern of p53 protein overexpression and the concordance of common p53 mutational patterns between the gastric EC and adenocarcinoma components. Expression of p53 was associated with a high degree of cell proliferation (Ki-67-positive nuclear cells) and this marker was able to predict a shorter survival time [5].…”
Section: Introductionmentioning
confidence: 96%
“…This highlights the need to better understand the behavior of GCs and to precisely classify them. 22 After all, how do we identify those patients with small type I GCs that have bad prognosis and should undergo surgical management? Should we base our decision on the grade provided by the 2010 WHO classification alone?…”
Section: Discussionmentioning
confidence: 99%
“…Of 270 genes differentially altered, CgA [30], MAGE-D2 (adhesin), MTA1 (histone deacetlyase regulator) [31] and CCN2 (growth factor) [20] can differentiate between type III and I tumours. Mutation of the tumour suppressor gene p53 has been reported to be strongly correlated with type III tumours and functionally may play a role in stimulating proliferation [32].…”
Section: Type III Gastric Netsmentioning
confidence: 99%